2002
DOI: 10.5271/sjweh.691
|View full text |Cite
|
Sign up to set email alerts
|

Work-schedule characteristics and reported musculoskeletal disorders of registered nurses

Abstract: The following article refers to this text: 2014;40(4):331-436

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
121
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(140 citation statements)
references
References 46 publications
15
121
2
2
Order By: Relevance
“…[58,60] Musculoskeletal disorders were found to be related to 12-hour shifts in this review, despite the fact that this finding had not previously been described in the literature. Although [25] produced the only study that recognized the relationship between work schedule characteristics and musculoskeletal disorders in day shifts; this finding is supported by another study identifying that long working hours are one of the risk factors of back pain; however, it should be noticed that this study did not define long hours as being of 12-hour or more. [61] The work schedule characteristics which included days of work, length of day, work breaks, and psychological demands were significantly associated with musculoskeletal disorders in the current finding.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…[58,60] Musculoskeletal disorders were found to be related to 12-hour shifts in this review, despite the fact that this finding had not previously been described in the literature. Although [25] produced the only study that recognized the relationship between work schedule characteristics and musculoskeletal disorders in day shifts; this finding is supported by another study identifying that long working hours are one of the risk factors of back pain; however, it should be noticed that this study did not define long hours as being of 12-hour or more. [61] The work schedule characteristics which included days of work, length of day, work breaks, and psychological demands were significantly associated with musculoskeletal disorders in the current finding.…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, the 12-hour shift group were more tired after sleep than the 8 hour shift group, despite the fact that they slept longer and had a higher ratio of average sleep length, to the length of sleep declared as sufficient (0.84) in the 8-hour shift group (0.62). Lipscomb et al (2002) carried out a study to examine the relationship between work schedule characteristics such as working for 12-hour shifts or more per week (day shift), and 8-hour shifts or more per week (day shift), and the reported musculoskeletal disorders of the neck, shoulders, and back. [25] This cross-sectional study had a sample of 1,163 nurses selected randomly from the list of actively licensed nurses residing in two states, Illinois and New York, United States.…”
Section: Figure 1 Search and Retrieval Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Working long hours was also linked with MS pain among homemakers. This mirrors studies of nurses, who were more likely to experience MS pain when working overtime, at weekends, or during off times (Lipscomb et al 2002, Trinkoff et al 2006. A review of work-schedule issues among healthcare workers found that working extended and difficult schedules may be associated with MS pain (Caruso and Waters 2008).…”
Section: Comparisons and Contributions To The Literaturementioning
confidence: 52%
“…Thus, not only does a high workload affect nurse wellbeing, it also affects patient wellbeing. Similar results have been found for those U.S. nurses who work demanding schedules such as working longer than 12 hours, more than 40 hours per week, and "off hours" such as weekends and nights (Lipscomb, Trinkoff, Geiger-Brown, & Brady, 2002;Trinkoff, Le, Geiger-Brown, Lipscomb, & Lang, 2006). Nurses that reported demanding work schedules were more likely to report musculoskeletal injuries in their neck, shoulder, and back.…”
Section: Summary Of Results and Contributionssupporting
confidence: 78%